Mesoporous magnetic biochar derived from common reed (Phragmites australis) for rapid and efficient removal of methylene blue from aqueous media - Wael Ibrahim Mortada; Mahmoud Mohsen Ghaith; Nada Elsayed Khedr; Mostafa Ibrahim Ellethy; Alaa Waleed Mohsen; Amira Labib Shafik (Environmental Science and Pollution Research, 2024)
A novel mesoporous magnetic biochar (MBC) was prepared, using a randomly growing plant, i.e., common reed, as an exporter of carbon, and applied for removal of methylene blue (MB) from aqueous solutions. The prepared sorbent was characterized by nitrogen adsorption/desorption isotherm, saturation magnetization, pH of point of zero charges (pH PZC ), Fourier-transform infrared spectroscopy (FT-IR), and scanning electron microscopy (SEM). The obtained MBC has a specific surface area of 94.2 m 2 g −1 and a pore radius of 4.1 nm, a pore volume of 0.252 cm 3 g −1 , a saturation magnetization of 0.786 emu g −1 , and a pH PZC of 6.2. Batch adsorption experiments were used to study the impact of the physicochemical factors involved in the adsorption process. The findings revealed that MB removal by MBC was achieved optimally at pH 8.0, sorbent dosage of 1.0 g L −1 , and contact time of 30 min. At these conditions, the maximum adsorption was 353.4 mg g −1 . Furthermore, the adsorption isotherm indicated that the Langmuir pattern matched well with the experimental data, compared to the Freindlich model. The ∆ G was − 6.7, − 7.1, and − 7.5 kJ mol −1 , at 298, 308, and 318 K, respectively, indicating a spontaneous process. The values of ∆ H and ∆ S were 5.71 kJ mol −1 and 41.6 J mol −1 K −1 , respectively, suggesting endothermic and the interaction between MB and MBC is van der Waals type. The absorbent was regenerated and reused for four cycles after elution with 0.1 mol L −1 of HCl. This study concluded that the magnetic biochar generated from common reed has tremendous promise in the practical use of removing MB from wastewater. Graphic Abstract